Influence of Interpersonal and Institutional Trust on the Participation Willingness of Farmers in E-Commerce Poverty Alleviation - Chen, Guoyi; Tan, Wei; Zhang, Shangmin; Yan, Bangquan (Frontiers in Psychology, 2021)
In order to explore the influence of interpersonal trust and institutional trust on the farmers’ participation willingness of E-commerce Poverty Alleviation in China, A questionnaire survey of 320 farmers in Chongqing Ecological Tourism District was adopted for data collection, and Binary logistic model was used for data analysis. Results showed that (1) both interpersonal trust and institutional trust all had positive influence on farmers' participation behavior of E-commerce Poverty Alleviation, and the priority ranking from high to low was: trust in government, trust in relatives, trust in neighbors and trust in village cadres. (2) Institutional trust had a greater impact on farmers' participation behavior than interpersonal trust, especially in the poverty stricken areas where economic development was relatively backward. (3) Individual attributes, Household attributes and rural resource attributes also had a significant positive impact on farmers' participation intention. Among these, the role of Rural E-business service platform was particular important. The role of institutional trust at the village level still did not perform well in promoting farmers' participation willingness. Based on empirical analysis, suggestions for promoting farmers' active cooperation and participating in the cooperation of e-business were put forward, including enhancing farmers' interpersonal network, improving rural e-commerce information service platform and strengthening the construction of rural business environment.